2013
DOI: 10.3126/ajms.v5i1.8474
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemia and its Relationship with Cardiovascular Risk Factors in a Selected Population of Siliguri City, West Bengal, India.

Abstract: Background:Dyslipidemia, one of the classical Framingham risk factors of cardiovascular diseases, accounts significantly to the rise of non communicable diseases in India. Urbanization, along with greater consumption of dietary fats and decreased physical activity, has led to an increase in this problem manifold. Objectives: To determine the prevalence of dyslipidemia among urban adults of Siliguri city, West Bengal and to identify the cardio-vascular risk factors associated with it.Methods: This descriptive, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 17 publications
6
3
1
Order By: Relevance
“…The prevalence of high LDL-C (49.5%) in this study is higher than the previous finding reported in Ethiopia (14.1%) [30]. It is almost similar to study findings reported in India (47.8%) [26] and Iran (50.0%) [31]. But lower than the findings reported in Thailand (56.5%) [32], Uganda (60.9%) [33], Ghana (61.0%) [34], Senegal (66.3%) [35], and Jordan (75.9%) [36].…”
Section: Plos Onesupporting
confidence: 84%
See 1 more Smart Citation
“…The prevalence of high LDL-C (49.5%) in this study is higher than the previous finding reported in Ethiopia (14.1%) [30]. It is almost similar to study findings reported in India (47.8%) [26] and Iran (50.0%) [31]. But lower than the findings reported in Thailand (56.5%) [32], Uganda (60.9%) [33], Ghana (61.0%) [34], Senegal (66.3%) [35], and Jordan (75.9%) [36].…”
Section: Plos Onesupporting
confidence: 84%
“…However, the prevalence of dyslipidemia in this study is higher than the previous findings reported in Eastern Ethiopia (34.8%) [11], Africa PLOS ONE (25.5%) [9], China (32.2%) [20], Iran (30.0%) [21], India (50.7%) [22], and Uganda (63.3%) [23]. Contrary to this, the prevalence is lower than previous studies reported in Lithuania (89.7%) [24], South Africa (85.0%) [25], India (78.4%) [26] and Poland (77.2%) [27]. This difference might be due to variation in the cutoffs, stage of urbanization in the various study settings, study period, socioeconomic status, and lifestyles of the study subjects.…”
Section: Plos Onementioning
confidence: 59%
“…This finding is in agreement with previous studies conducted in India (50.7%) [ 24 ]. However, this finding is lower than the previous similar studies conducted in Poland (77.2%) [ 28 ], Lithuania (89.7%) [ 29 ], Palestine (66.4%) [ 30 ], South Africa (67.3%) [ 31 ], India (78.4%) [ 32 ], Uganda (63.3%) [ 33 ], South Africa (85.0%) [ 34 ]. In contrast, the current finding is higher than previous studies done in China (32.2%) [ 35 ], Ethiopia (34.8%) [ 13 ], and Iran (30.0%) [ 36 ].…”
Section: Discussioncontrasting
confidence: 58%
“…Ghana (61.0%) [ 56 ]. India (47.8%) [ 32 ], Senegal (66.3%) [ 57 ], Iran (50.0%) [ 58 ], and Uganda (60.9%) [ 47 ]. However, the current finding is higher than previous similar studies done in Ethiopia (14.1%) [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The process of this disease begins early in life and gradually progresses throughout the following years (8). Hyperlipidemia is an important risk factor for cardiovascular disease (9). A strong independent relationship between childhood and adulthood serum lipids has been reported (10).…”
Section: Introductionmentioning
confidence: 99%